2009
DOI: 10.1063/1.3270389
|View full text |Cite
|
Sign up to set email alerts
|

Robust extremes in chaotic deterministic systems

Abstract: This paper introduces the notion of robust extremes in deterministic chaotic systems, presents initial theoretical results, and outlines associated inferential techniques. A chaotic deterministic system is said to exhibit robust extremes under a given observable when the associated statistics of extreme values depend smoothly on the system's control parameters. Robust extremes are here illustrated numerically for the flow of the Lorenz model [E. N. Lorenz, J. Atmos. Sci. 20, 130 (1963)]. Robustness of extremes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Obviously, it is of crucial relevance, for both mathematical reasons and for devising a working framework to be used in applications, to understand under which circumstances the time series of observables of deterministic dynamical systems can be treated using the EVT. Empirical studies show that in some cases, the extremes of dynamical observables of chaotic systems obey up to a high degree of precision the GEV statistics, even if it is apparent that the asymptotic convergence is highly dependent on the considered observables (Felici et al, 2007;Vannitsem 2007;and Vitolo et al, 2009a;2009b). Instead, Balakrishnan et al (1995) and, more recently, Nicolis et al (2006) showed that when considering a dynamical system featuring a regular (periodic or quasiperiodic) motion, the extremes of a generic dynamical observable do not obey any statistics compatible with those of GEV distributions.…”
Section: B Extreme Value Theory For Dynamical Systemsmentioning
confidence: 98%
“…Obviously, it is of crucial relevance, for both mathematical reasons and for devising a working framework to be used in applications, to understand under which circumstances the time series of observables of deterministic dynamical systems can be treated using the EVT. Empirical studies show that in some cases, the extremes of dynamical observables of chaotic systems obey up to a high degree of precision the GEV statistics, even if it is apparent that the asymptotic convergence is highly dependent on the considered observables (Felici et al, 2007;Vannitsem 2007;and Vitolo et al, 2009a;2009b). Instead, Balakrishnan et al (1995) and, more recently, Nicolis et al (2006) showed that when considering a dynamical system featuring a regular (periodic or quasiperiodic) motion, the extremes of a generic dynamical observable do not obey any statistics compatible with those of GEV distributions.…”
Section: B Extreme Value Theory For Dynamical Systemsmentioning
confidence: 98%
“…Until now, rigorous results have been obtained assuming the existence of an invariant measure for the dynamical systems and the fulfillment of independence requirement on the series of maxima achieved by imposing D ′ and D 2 mixing conditions, or, alternatively, assuming an exponential hitting time statistics [22][23][24][25]. The parameters of the GEV distribution obtained choosing as observables the function g i , i = 1, 2, 3 defined above depend on the local dimension of the attractor D and numerical algorithms to perform statistical inference can be set up for mixing systems having both absolutely continuous and singular invariant measures [27,28,39,40]. Instead, when considering systems with regular dynamics, the statistics of the block maxima of any observable does not converge to the GEV family [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Maximum likelihood is a common estimation method [10]: in this case, standard asymptotic theory also provides confidence intervals (uncertainties) for the point estimates. The estimated GEV parameters and associated uncertainties can then be used to derive other quantities of interest, such as return periods for given return levels of the variable of interest, see the above references and [16,17,52,53] for examples.…”
Section: Background On Extreme Value Theorymentioning
confidence: 99%